Associations of Serum Mineral levels of Copper, Magnesium and Calcium with Skeletal Muscle mass and Strength in Chinese children, aged 6-11: A Cross-Sectional Study - Abubakar Tarawally; Zheqing Zhang; Unami Japhta-Mlandu (Health Dynamics, 2024)
Background:Skeletal Muscle Mass (SMM) and strength are crucial for children's health, and low SMM can lead to adverse health outcomes. A deficiency of essential minerals can cause poor growth, fractures or osteoporosis. The study aimed to explore the relationship between serum Calcium (Ca), Copper (Cu), and Magnesium (Mg) levels and SMM in Chinese children.Methods:466 primary school children were recruited for a cross-section study aged 6-11 in Guangzhou City, South of China, from December 2015 to February 2017. The study conducted whole-body dual-energy x-ray absorptiometry (DXA) scans using the Hologic discovery W to obtain the Total skeletal mass (TSM) and appendicular skeletal mass (ASM) were calculated, which were used as parameters to calculate variables of Skeletal muscle mass (SMM).Results:Of the 466 primary school children, 266 were boys and 200 girls with mean ages of 8.001.00 years for boys and 8.080.97 years for girls. An increase in mean Cu serum concentration between the T1 and T3 in girls resulted in 3.19% (P- trend =0.034, P-diff =0.083), 3.57% (P- trend =0.037, P-diff=0.083), 2.44% (P- trend =0.018, P=diff=0.060) and 2.25% (P- trend =0.024, P-diff= 0.072) for ASM/Height, ASH/ Weight, TSM/ Height and TSM/ Weight respectively, No significant mean difference was observed between serum Cu and ASM, TSM, ASM/ AFM and TSM/TFM (P- trend >0.05). A significant mean difference in serum Mg levels and ASM/ AFM for the total and boys' group was observed, with 6.68% and 9.44% (P- trend =0.042 and 0.041) respectively. No significant mean differences were seen between all the variables of serum Ca levels and all the variables of skeletal muscle mass and strength.Conclusions:Serum copper levels influence the development of SMM in girls, but not in boys. Serum Ca and Mg level in girls and boys do not influence SMM development among children aged 6-11.